2016
DOI: 10.7448/ias.19.1.20714
|View full text |Cite
|
Sign up to set email alerts
|

TB as a cause of hospitalization and in‐hospital mortality among people living with HIV worldwide: a systematic review and meta‐analysis

Abstract: IntroductionDespite significant progress in improving access to antiretroviral therapy over the past decade, substantial numbers of people living with HIV (PLHIV) in all regions continue to experience severe illness and require hospitalization. We undertook a global review assessing the proportion of hospitalizations and in-hospital deaths because of tuberculosis (TB) in PLHIV.MethodsSeven databases were searched to identify studies reporting causes of hospitalizations among PLHIV from 1 January 2007 to 31 Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
92
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 26 publications
4
92
0
7
Order By: Relevance
“…TB is also a major cause of hospitalisation and in-hospital mortality in adults and children globally, and early ART is likely to substantially reduce this burden. 25 Second, there are plans to scale up IPT in a phased manner around the country. Two randomised controlled studies in Ivory Coast and South Africa have demonstrated that adding IPT to ART in PLHIV can lead to an additional reduction in TB cases of 30% or higher, 7,26 and this intervention may add to the TB preventive effect of ART.…”
Section: Public Health Action Declines In Tb With Art 250mentioning
confidence: 99%
“…TB is also a major cause of hospitalisation and in-hospital mortality in adults and children globally, and early ART is likely to substantially reduce this burden. 25 Second, there are plans to scale up IPT in a phased manner around the country. Two randomised controlled studies in Ivory Coast and South Africa have demonstrated that adding IPT to ART in PLHIV can lead to an additional reduction in TB cases of 30% or higher, 7,26 and this intervention may add to the TB preventive effect of ART.…”
Section: Public Health Action Declines In Tb With Art 250mentioning
confidence: 99%
“…Pathological autopsy studies involving HIV-positive individuals have consistently found tuberculosis (TB) to be the leading cause of death and the overall prevalence of active TB to be extremely high, much of it undiagnosed antemortem [47]. The World Health Organization (WHO) aims to reduce TB deaths by 95% by 2035 [8], but questions remain around current estimates of TB deaths and the methods used to obtain them [9].…”
Section: Introductionmentioning
confidence: 99%
“…Among these patients, approximately 10% die during the first 3 months after ART initiation 58. Causes of death are multifactorial and similar between adults and older children,7 with severe bacterial infection,3,9 tuberculosis,8,10,11 and cryptococcal infection12,13 playing prominent roles. The development or exacerbation of such infections has been linked in part to the immune reconstitution inflammatory syndrome (IRIS) associated with the initiation of ART.…”
mentioning
confidence: 99%